Hubungan Media Internet Sebagai Sumber Pembelajaran PPKn Terhadap Prestasi Belajar Siswa Kelas VIII di SMP Adhyaksa Medan - Pardede, Lukman; Simanjuntak, Hotmaida; Pasaribu, Kondios Mei Darlin; Nainggolan , Juliper; Siahaan, Monalisa Marta; Tampubolon, Anisa Putri Roma Yana Br (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine the influence of internet media as a source of PPKn learning on the learning achievement of class VIII students at Adhyaksa Middle School, Medan, academic year 2023/2024. This research aims to examine the influence of internet media as a source of PPKn learning on the learning achievement of class VIII students at Adhyaksa Middle School, Medan, for the 2023/2024 academic year. The population in this study was Adhyaksa Medan Middle School students using non-random sampling. The sample in this research was Class VIII students with a total of 50 students. The data collection method is through a questionnaire totaling 20 questions for Internet Media, while Learning Achievement is obtained through documentation (Report Scores). The product moment calculation results show that the correlation number between variable X and variable Y is positive, considering the magnitude of rxy obtained, namely 0.6411. Next, to find out whether the relationship is significant or not, the calculated r results are compared with the r table, with r 5% of 0.5140. If you look at the r table, it turns out that rxy is 0.6411. Greater than in the r table, with a significance level of 5%. Thus, the Alternative Hypothesis (Ha) is accepted, and the Null Hypothesis (H0) is rejected, meaning: